Nanoparticle synthesis of La1-xSrxMnO3 (0.1, 0.2 and 0.3) perovskites - Marques, RFC; Jafelicci, M.; Paiva-Santos, C. O.; Jardim, R. F.; Souza, J. A.; Varanda, L. C.; Godoi, RHM (Institute of Electrical and Electronics Engineers (IEEE), 2002)
Synthesis of La1-xSrxMnO3 (x = 0.1, 0.2 and 0.3) by homogenous coprecipitation method using urea as precipitant agent Is reported. The particles are smaller than 200 nm after heating at 950 degreesC. Temperature dependence of the electrical resistivity was found to be similar to the reported value for single crystals of these manganites.
Keywords: electrical resistivity; lanthanum strontium-doped manganite; nanoparticle; perovskite structure